Exploring The Theory Of Financial Innovation In The Context Of Industry 4.0 - Rolando, Benediktus; Mulyono, Herry; Hartanti, Rina; Ingriana, Alberta Ingriana (Abadi Institute, 2024)
The fourth industrial revolution, also known as Industry 4.0 is marked by rapid technological advancements that have significantly impacted various economic sectors, including the financial industry. This paper analyze how financial innovation is shaping the industry in the context of the 4.0 industrial revolution. The study explores the concept of financial innovation and its role in driving the transformation of the financial sector, particularly in the face of emerging technologies such as artificial intelligence, big data, and the Internet of Things. In this research, we utilized the Systematic Literature Review method to analyze over 100 articles from through platforms like Scopus, ScienceDirect, Google Scholar, Taylor & Francis Online, Wiley Online Library, and Copernicus International Index. Which formed the basis of our study results. The findings suggest that financial innovation is a key enabler for the digitalization of financial services, leading to the development of new business models, products, and services. Moreover, the integration of financial innovation with Industry 4.0 technologies has the potential to enhance efficiency, accessibility, and inclusivity in the financial sector. While the integration of financial innovation with Industry 4.0 technologies may indeed bring about efficiency and accessibility in the financial sector, it is important to consider the potential drawbacks and risks associated with this trend. This research is beneficial for academics, policymakers, and financial industry professionals who seek to understand the implications of financial innovation in the context of the fourth industrial revolution.